Longevity effects of hispidol in Caenorhabditis elegans. (12th November 2020) - Lim, Hyun Joo; Han, Young Taek; Ahn, Ji‐Hye; Jeon, Yong‐Deok; Jeon, Hoon; Cha, Dong Seok
Abstract: In this study, we investigated the longevity effects of hispidol, a 6, 4′‐dihydroxyaurone, using the Caenorhabditis elegans model system. Our lifespan assay data revealed that hispidol could prolong the lifespan of wild‐type worms under normal culture condition. Moreover, hispidol increased the survival rate of the worms against a heat stress condition through up‐regulated expressions of HSP‐16.2. Similarly, hispidol protected worms from paraquat‐induced oxidative stress. We also found that the hispidol elevated the activities of antioxidant enzymes, thereby attenuating the generation of intracellular reactive oxygen species. These results suggest that the enhancement of lifespan and stress resistance by the hispidol treatment might be attributed to its strong in vivo antioxidant capacity and regulation of stress proteins. Further tests on the aging‐related factors revealed that hispidol could regulate the speed of pharyngeal pumping, indicating the association of dietary restriction with the hispidol‐mediated longevity. However, there were no significant alterations in the body length of the worms between the groups. We then investigated the effects of hispidol on body movement and lipofuscin accumulation in aged worms. Interestingly, these healthspan parameters were strongly improved by the hispidol treatment. Our genetic studies showed no significant change in the lifespan of the daf‐16 null mutants by hispidol supplementation. In addition, enhanced nuclear translocation of DAF‐16 was observed in the hispidol‐fed DAF‐16::GFP fused transgenic mutants, suggesting the requirement of DAF‐16/FOXO activation for the longevity effect of hispidol.